PVDF-GO / TiO2 composite film as well as preparation method and application thereof

Through the preparation of PVDF-GO/TiO2 composite film, combined with the synergistic effect of light and stirring, the problems of difficult mineralization in dye wastewater treatment and low efficiency of traditional photocatalytic materials are solved, and efficient and environmentally friendly degradation of organic pollutants is achieved. Excellent mechanical properties and porous structure, suitable for large-scale production.

CN119237022AInactive Publication Date: 2025-01-03BEIJING HANTONG TECHNOLOGY CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202411366487.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The prior art has problems such as difficult to mineralize when treating dye wastewater, non-destructive treatment methods have secondary pollution, narrow photoresponse range of traditional photocatalytic materials, low quantum efficiency, and difficult to recover, and biological methods may be under anaerobic conditions. Produce carcinogens.

Method used

The PVDF-GO/TiO2 composite film was prepared by phase conversion method. The photocatalyst TiO2 was uniformly distributed in the PVDF matrix. Combined with the piezoelectric effect, the synergistic effect of light and stirring was used to achieve efficient degradation of organic pollutants.

Benefits of technology

It achieves efficient catalytic performance, excellent mechanical properties, porous structure and environmental protection, and can efficiently degrade organic pollutants under low frequency and weak force. The film is easy to recycle, avoids secondary pollution, is low-cost and is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119237022A_ABST
    Figure CN119237022A_ABST
Patent Text Reader

Abstract

The invention discloses a PVDF-GO / TiO2 composite film as well as a preparation method and application thereof, and belongs to the technical field of functional film materials. The preparation method of the PVDF-GO / TiO2 composite film comprises the following steps: adding PVDF into an organic solvent, dissolving, adding water, and uniformly mixing to obtain a precursor solution; and adding TiO2 and GO dispersion liquid into the precursor solution, uniformly dispersing to obtain a mixed solution, and spraying the mixed solution on the surface of a base material to obtain the PVDF-GO / TiO2 composite film. The PVDF-GO / TiO2 composite film disclosed by the invention has the advantages of efficient catalytic performance, excellent mechanical property, porous structure, environmental friendliness, simple preparation method (spraying film formation) and low manufacturing cost, and is expected to realize large-scale production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of functional membrane materials, and in particular to a PVDF-GO / TiO2 composite film and a preparation method and application thereof. Background Art

[0002] With the rapid development of chemical industries such as pesticides, dyes, and petrochemicals, environmental pollution problems have become increasingly serious. Among them, printing and dyeing wastewater has become one of the most important sources of water pollution. Especially in recent years, with the rapid development of dye preparation industry and dye application, the types of dyes and auxiliaries have become increasingly numerous, and most of them are difficult to degrade. Some of them also contain carcinogens such as benzene rings, amines, and azo groups, which have increased the difficulty of dye wastewater treatment. Some traditional treatment methods, such as coagulation and sedimentation, adsorption, membrane separation, and flotation are non-destructive physical treatment methods. They only transfer dyes between phases, and do not really mineralize dyes. There are also problems such as secondary pollution and adsorbent regeneration, which have not been reasonably solved. There are also problems with the use of biological methods to treat dye wastewater. It is not easy to biodegrade under aerobic conditions, and under anaerobic conditions, dyes are easily converted into carcinogens such as aromatic amines, which pose a huge threat to human health, and the treatment time is relatively long.

[0003] Photocatalytic technology has attracted extensive attention because it can catalytically decompose organic pollutants under light conditions. Compared with other biological and chemical treatment methods, this technology has the characteristics of high efficiency, low energy consumption, simple operation, mild reaction conditions, wide application range, non-toxicity and no secondary pollution. However, traditional photocatalytic materials (such as titanium dioxide (TiO2), zinc oxide (ZnO), etc.) have problems such as narrow light response range, low quantum efficiency, and difficulty in recycling, which limit their practical application. Summary of the invention

[0004] The purpose of the present invention is to provide a PVDF-GO / TiO2 composite film and its preparation method and application to solve the problems existing in the above-mentioned prior art. The PVDF-GO / TiO2 composite film of the present invention is a flexible porous PVDF-based composite piezoelectric photocatalytic film, which is prepared by a phase inversion method, and the photocatalyst (TiO2) is uniformly distributed in the PVDF matrix as a filler, and has excellent photocatalytic degradation of organic pollutants.

[0005] To achieve the above object, the present invention provides the following solutions:

[0006] One of the technical solutions of the present invention: a method for preparing a PVDF-GO / TiO2 composite film, comprising the following steps:

[0007] PVDF is added to an organic solvent to dissolve, and then water is added and mixed to obtain a precursor solution;

[0008] TiO2 and GO dispersions are added to the precursor solution and dispersed evenly to obtain a mixed solution, and the mixed solution is sprayed on the surface of the substrate to obtain the PVDF-GO / TiO2 composite film.

[0009] Further, the PVDF includes PVDF-HFP;

[0010] The usage ratio of the PVDF, organic solvent and water is 0.477 g:12 ml:0.477 ml;

[0011] The amount of TiO2 is 5-15% of the mass of PVDF;

[0012] The dosage ratio of the PVDF and GO dispersion is 0.477 g: 0.1-1 ml;

[0013] The proportion of GO in the GO dispersion is 5 wt %.

[0014] Furthermore, the ratio of the spraying amount of the mixed solution to the area of ​​the substrate is 4-18 ml: 100 cm 2 .

[0015] The second technical solution of the present invention: a PVDF-GO / TiO2 composite film prepared by the above preparation method.

[0016] The third technical solution of the present invention: an application of the above-mentioned PVDF-GO / TiO2 composite film in photocatalytic degradation of organic pollutants.

[0017] Furthermore, the organic pollutants include dyes or antibiotics.

[0018] Technical solution 4 of the present invention: A method for piezoelectric photocatalytic degradation of organic pollutants in water, comprising the following steps:

[0019] The PVDF-GO / TiO2 composite film is placed in an aqueous solution containing organic pollutants and subjected to piezoelectric photocatalytic degradation under illumination and stirring.

[0020] Furthermore, the illumination is full spectrum illumination with a light intensity of 1000W / cm 2 ;

[0021] The stirring speed is 1000-1400 rpm.

[0022] Piezoelectric photocatalytic degradation mechanism: First, light excites the PVDF-GO / TiO2 composite film (catalyst) to produce photogenerated electron-hole pairs, and the electrons transfer from the valence band of TiO2 to the conduction band, and further migrate to the catalyst surface for reduction reaction, forming active oxygen (hydroxyl radicals and superoxide radicals). Subsequently, the active oxygen participates in the degradation of organic pollutants and decomposes them into small molecules. Secondly, stirring causes the deformation of the PVDF-based composite film, and under the action of external force, a piezoelectric field is induced inside the film, which promotes the transfer of electrons inside the catalyst to the surface, which is conducive to the generation of active oxygen. The synergistic effect of piezoelectricity and light promotes the degradation of organic pollutants, making it possible to achieve efficient degradation of organic pollutants without the addition of sacrificial agents.

[0023] GO and TiO2 can induce the formation of β phase of PVDF, and GO can broaden the light absorption utilization range of TiO2, promote the adsorption of dyes, and improve the degradation effect of pollutants.

[0024] The present invention discloses the following technical effects:

[0025] (1) The PVDF-GO / TiO2 composite film prepared by the present invention has high-efficiency catalytic performance: by introducing a photocatalyst and combining it with the piezoelectric effect of PVDF, the catalytic efficiency of the film is significantly improved, and it can achieve efficient degradation of organic pollutants under the action of low-frequency weak forces, and is expected to play an important role in practical applications.

[0026] Excellent mechanical properties: PVDF-based composite film has good flexibility, can adapt to various complex working environments, and is not easy to break. It can be deformed and generate polarization under weak forces such as stirring and water flow.

[0027] Porous structure: The film prepared by the phase inversion method has a porous structure, which is beneficial to increase the specific surface area of ​​the photocatalyst and further improve the photocatalytic performance.

[0028] Environmentally friendly: Compared with powdered catalysts, film materials are easy to recycle, saving recycling costs and being environmentally friendly. The film material itself is non-toxic and will not cause secondary pollution to the environment during use.

[0029] (2) The preparation method of the PVDF-GO / TiO2 composite film of the present invention is simple (spraying film formation), the production cost is low, and it is expected to achieve large-scale production.

[0030] (3) The PVDF-GO / TiO2 composite film prepared by the present invention is a composite film that can induce the formation of a high β-phase content (GO and TiO2 can induce the formation of the β-phase of PVDF), which can improve the piezoelectric response ability of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0032] Figure 1 The Raman spectra of the raw material PVDF used in the present invention, the PVDF-GO prepared in Comparative Example 1, the PVDF-TiO2 prepared in Comparative Example 2, and the PVDF-GO / TiO2 composite film prepared in Example 4;

[0033] Figure 2 XRD patterns of the raw material PVDF used in the present invention, the PVDF-GO prepared in Comparative Example 1, the PVDF-TiO2 prepared in Comparative Example 2, and the PVDF-GO / TiO2 composite film prepared in Example 4;

[0034] Figure 3 The d of the raw material PVDF used in the present invention, the PVDF-GO prepared in Comparative Example 1, the PVDF-TiO2 prepared in Comparative Example 2, and the PVDF-GO / TiO2 composite film prepared in Example 4 33 ;

[0035] Figure 4 The piezoelectric photocatalytic degradation effect of rhodamine B and ciprofloxacin by the PVDF-GO / TiO2 composite film prepared in Examples 1 to 5 of the present invention, wherein A is rhodamine B and B is ciprofloxacin;

[0036] Figure 5 The active oxygen and hydroxyl radical production of the PVDF-GO / TiO2 composite film prepared in Examples 1 to 5 of the present invention under the combined action of piezoelectricity and light;

[0037] Figure 6 The piezoelectric photocatalytic degradation effect of rhodamine B and ciprofloxacin by PVDF-GO / TiO2 composite films of different thicknesses prepared by the present invention, wherein A is rhodamine B and B is ciprofloxacin;

[0038] Figure 7 The production of active oxygen and hydroxyl radicals of PVDF-GO / TiO2 composite films of different thicknesses prepared by the present invention under the combined action of piezoelectricity and light;

[0039] Figure 8 The piezoelectric photocatalytic degradation effect of rhodamine B and ciprofloxacin by the PVDF-GO / TiO2 composite film prepared by the present invention under different stirring conditions, wherein A is rhodamine B and B is ciprofloxacin;

[0040] Fig. 9 The production of active oxygen and hydroxyl radicals of the PVDF-GO / TiO2 composite film prepared by the present invention under different stirring conditions and the combined action of piezoelectricity and light;

[0041] Fig.10 The piezoelectric photocatalytic degradation effect of Rhodamine B by the raw material PVDF used in the present invention, the PVDF-GO prepared in Comparative Example 1, the PVDF-TiO2 prepared in Comparative Example 2, and the PVDF-GO / TiO2 composite film prepared in Example 4;

[0042] Fig.11 The piezoelectric photocatalytic degradation effect of ciprofloxacin by the raw material PVDF used in the present invention, the PVDF-GO prepared in Comparative Example 1, the PVDF-TiO2 prepared in Comparative Example 2, and the PVDF-GO / TiO2 composite film prepared in Example 4;

[0043] Fig.12 The piezoelectric photocatalytic degradation effect of Rhodamine B by the PVDF-GO / TiO2 composite film (PVDF-GO / TiO2) prepared in Example 4 of the present invention, the non-porous PVDF-GO / TiO2 film prepared in Comparative Example 4, and the porous PVDF-GO / TiO2 film prepared in Comparative Example 5;

[0044] Fig.13 The piezoelectric photocatalytic degradation effect of Rhodamine B by the PVDF-GO / TiO2 composite film prepared in Example 4 of the present invention, the PVDF-C / TiO2 composite film prepared in Comparative Example 7, and the PVDF-GO / BaTiO3 composite film prepared in Comparative Example 8. DETAILED DESCRIPTION

[0045] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0046] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0047] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0048] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.

[0049] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.

[0050] PVDF-HFP was purchased from Sigma-Aldrich with an average Mw of 400,000 and an average Mn of 130,000.

[0051] Example 1

[0052] A PVDF-GO / TiO2 composite film and preparation method thereof:

[0053] (1) 0.477 g of PVDF-HFP particles were placed in 12 ml of acetone, heated at 60° C. and stirred until dissolved, and then 0.477 g of deionized water (the mass ratio of PVDF-HFP, acetone and water was 1:20:1) was added and mixed evenly to obtain a precursor solution.

[0054] (2) Add TiO2 (the amount of TiO2 is 5% of the mass of PVDF-HFP) and 0.1 ml of GO dispersion (the mass ratio of GO to water in the GO dispersion is 5:95) to the precursor solution, stir until uniformly dispersed, and obtain a PVDF-GO / TiO2 mixed solution.

[0055] (3) Take 4 ml of PVDF-GO / TiO2 mixed solution and pour it into a glass bottle, and spray it on the surface of 10 cm×10 cm aluminum foil to obtain a PVDF-GO / TiO2 composite film, which is recorded as PVDF-GO / TiO2 (0.1 ml / 5 wt%).

[0056] Example 2

[0057] The same as Example 1, except that the amount of GO dispersion used in step (2) is 0.5 ml, and the PVDF-GO / TiO2 composite film is obtained, which is recorded as PVDF-GO / TiO2 (0.5 ml / 5 wt%).

[0058] Example 3

[0059] The same as Example 1, except that the amount of GO dispersion used in step (2) is 1 ml, and the obtained PVDF-GO / TiO2 composite film is recorded as PVDF-GO / TiO2 (1 ml / 5 wt%).

[0060] Example 4

[0061] The same as Example 3, except that the amount of TiO2 used in step (2) is 10% of the mass of PVDF-HFP, and a PVDF-GO / TiO2 composite film is obtained, which is recorded as PVDF-GO / TiO2 (1 ml / 10wt%).

[0062] Example 5

[0063] The same as Example 3, except that the amount of TiO2 used in step (2) is 15% of the mass of PVDF-HFP, and a PVDF-GO / TiO2 composite film is obtained, which is recorded as PVDF-GO / TiO2 (1 ml / 15wt%).

[0064] Example 6

[0065] Same as Example 4, except that the amount of PVDF-GO / TiO2 mixed solution used in step (3) is 10 ml.

[0066] Example 7

[0067] Same as Example 4, except that the amount of PVDF-GO / TiO2 mixed solution used in step (3) is 18 ml.

[0068] Comparative Example 1

[0069] Preparation method of PVDF-GO:

[0070] (1) 0.477 g of PVDF-HFP particles were placed in 12 ml of acetone, heated at 60° C. and stirred until dissolved, and then 0.477 g of deionized water (the mass ratio of PVDF-HFP, acetone and water was 1:20:1) was added and mixed evenly to obtain a precursor solution.

[0071] (2) Add GO powder (the amount of GO powder is 10% of the mass of PVDF-HFP) and 1 ml of GO dispersion (the mass ratio of GO to water in the GO dispersion is 5:95) to the precursor solution, stir until uniformly dispersed, and obtain a PVDF-GO mixed solution.

[0072] (3) Pour 4 ml of the PVDF-GO mixed solution into a glass bottle and spray it on the surface of a 10 cm × 10 cm aluminum foil to obtain a PVDF-GO composite film, which is recorded as PVDF-GO.

[0073] Comparative Example 2

[0074] Preparation method of PVDF-TiO2:

[0075] (1) 0.477 g of PVDF-HFP particles were placed in 12 ml of acetone, heated at 60° C. and stirred until dissolved, and then 0.477 g of deionized water (the mass ratio of PVDF-HFP, acetone and water was 1:20:1) was added and mixed evenly to obtain a precursor solution.

[0076] (2) Add TiO2 (the amount of TiO2 is 10% of the mass of PVDF-HFP) and 1 ml of TiO2 dispersion (the mass ratio of TiO2 to water in the TiO2 dispersion is 5:95) to the precursor solution, stir until uniformly dispersed, and obtain a PVDF-TiO2 mixed solution.

[0077] (3) Pour 4 ml of the PVDF-TiO2 mixed solution into a glass bottle and spray it on the surface of a 10 cm × 10 cm aluminum foil to obtain a PVDF-TiO2 composite film, which is recorded as PVDF-TiO2.

[0078] The Raman spectra of the raw material PVDF (i.e., PVDF-HFP) used in the present invention, the PVDF-GO prepared in Comparative Example 1, the PVDF-TiO2 prepared in Comparative Example 2, and the PVDF-GO / TiO2 composite film prepared in Example 4 are shown in FIG. Figure 1 .

[0079] from Figure 1 As can be seen, 510cm -1 and 642cm -1 Corresponding to the Ti-O Raman vibration peak. 1354cm -1 and 1593cm -1 The CC and C=C Raman vibration peaks corresponding to GO indicate the successful preparation of PVDF-GO / TiO2 film.

[0080] The XRD spectra of the raw material PVDF (i.e., PVDF-HFP) used in the present invention, the PVDF-GO prepared in Comparative Example 1, the PVDF-TiO2 prepared in Comparative Example 2, and the PVDF-GO / TiO2 composite film prepared in Example 4 are shown in FIG. Figure 2 .

[0081] from Figure 2 It can be seen that the peaks at 18.3° and 20.2° correspond to the α-phase (020) plane and the β-phase (110) plane, respectively. Compared with the pure PVDF film, the addition of GO and TiO2 increases the α and β phase contents of the film, which is theoretically attributed to the simultaneous existence of the nanoconfinement effect.

[0082] The raw material PVDF (i.e., PVDF-HFP) used in the present invention, the PVDF-GO prepared in Comparative Example 1, the PVDF-TiO2 prepared in Comparative Example 2, and the PVDF-GO / TiO2 composite film prepared in Example 4 were subjected to quasi-static d 33 The measured value d 33 See Figure 3 .

[0083] from Figure 3 It can be seen that with the addition of GO and TiO2 33 It gradually increases, further indicating the positive effects of GO and TiO2 on the formation of PVDF-HFPβ phase. PVDF-GO / TiO2 has the highest d 33 Dielectric constant, indicating high piezoelectric responsiveness.

[0084] Example 8

[0085] A method for degrading organic pollutants in water by piezoelectric photocatalysis:

[0086] (1) Prepare 20 mg / L of Rhodamine B solution (simulating Rhodamine B wastewater, using deionized water for preparation) or 20 mg / L of ciprofloxacin solution (simulating ciprofloxacin wastewater, using deionized water for preparation), and take 20 ml of each in a beaker as the solution to be degraded. 20 mg of PVDF-GO / TiO2 (0.1 ml / 5 wt%), PVDF-GO / TiO2 (0.5 ml / 5 wt%), PVDF-GO / TiO2 (1 ml / 5 wt%), PVDF-GO / TiO2 (1 ml / 10 wt%), and PVDF-GO / TiO2 (1 ml / 15 wt%) prepared in Examples 1 to 5 were placed in Rhodamine B or ciprofloxacin (antibiotic) solution and illuminated (full spectrum, light intensity of 1000 W / cm 2) and stirring (1000rpm), the piezoelectric photocatalytic degradation experiment was carried out, the degradation time was 120min, 3ml of degradation solution was taken every 30min during the degradation process, and the absorbance of the degradation solution sample was tested on an ultraviolet visible spectrophotometer (UV-2600). After the test, the degradation solution sample was poured back into the beaker. The ratio of the absorbance at each time point in each group to the original absorbance (before degradation) was calculated, and the results are shown in Figure 4 , Figure 4 Figure A shows the effect of piezoelectric photocatalytic degradation of rhodamine B, and Figure B shows the effect of piezoelectric photocatalytic degradation of ciprofloxacin.

[0087] from Figure 4 As can be seen from Figure A, in the experiment of degrading Rhodamine B, PVDF-GO / TiO2 (1ml / 10wt%) has the best piezoelectric photocatalytic degradation ability, and the degradation rate can reach 99.3% after 30 minutes of reaction, while the degradation rates of PVDF-GO / TiO2 (0.1ml / 5wt%), PVDF-GO / TiO2 (0.5ml / 5wt%), PVDF-GO / TiO2 (1ml / 5wt%) and PVDF-GO / TiO2 (1ml / 15wt%) are 80.5%, 92%, 79.7% and 95.9% respectively.

[0088] from Figure 4 As can be seen from Figure B, PVDF-GO / TiO2 (1ml / 10wt%) also showed a relatively good degradation effect in the ciprofloxacin degradation experiment, with a degradation rate of up to 95.2% after 120 minutes of reaction, while the degradation rates of PVDF-GO / TiO2 (0.1ml / 5wt%), PVDF-GO / TiO2 (0.5ml / 5wt%), PVDF-GO / TiO2 (1ml / 5wt%) and PVDF-GO / TiO2 (1ml / 15wt%) were 79.9%, 81.7%, 92.1% and 96%, respectively.

[0089] (2) The active oxygen production of the PVDF-GO / TiO2 composite films prepared in Examples 1 to 5 under the combined action of piezoelectricity and light was tested, specifically:

[0090] The terephthalic acid photoluminescence method (TA-PL, concentration 0.5×10 -3 mol / L) was used to test the generation of ·OH free radicals. Nitro blue tetrazolium chloride (NBT, concentration of 2.5×10 -2 mol / L) tested ·O2 - The amount of free radicals generated.

[0091] The amount of OH radicals can be determined by measuring the fluorescence intensity at 425 nm using an excitation wavelength of 315 nm on a fluorescence spectrophotometer (F97XP, China). - The amount of free radicals can be measured by the absorbance of NBT using a UV-visible spectrophotometer (UV-2600).

[0092] The specific experimental steps are as follows: 20 mg of the PVDF-GO / TiO2 composite film prepared in Examples 1 to 5 was placed in 20 ml of TA solution or NBT solution, and then the film was irradiated with light (full spectrum, light intensity of 1000 W / cm 2 ) and stirring (1000rpm), the test was carried out. After 120min of piezoelectric photocatalytic degradation, 3ml of solution was taken and then tested on a fluorescence spectrophotometer (F97XP, China) or a UV-visible spectrophotometer (UV-2600). The test results are shown in Figure 5 .

[0093] Figure 5 0.1 / 5 is PVDF-GO / TiO2 (0.1ml / 5wt%) prepared in Example 1; 0.5 / 5 is PVDF-GO / TiO2 (0.5ml / 5wt%) prepared in Example 2; 1 / 5 is PVDF-GO / TiO2 (1ml / 5wt%) prepared in Example 3; 1 / 10 is PVDF-GO / TiO2 (1ml / 10wt%) prepared in Example 4; 1 / 15 is PVDF-GO / TiO2 (1ml / 15wt%) prepared in Example 5.

[0094] from Figure 5 It can be seen that the ·OH radicals and ·O2 - The production of free radicals is different, among which PVDF-GO / TiO2 (1 ml / 10 wt%) and PVDF-GO / TiO2 (1 ml / 15 wt%) produce ·OH radicals and ·O2 - The free radical content is relatively high, which is basically consistent with the degradation results.

[0095] Example 9

[0096] A method for degrading organic pollutants in water by piezoelectric photocatalysis:

[0097] (1) Prepare 20 mg / L of rhodamine B solution (simulated rhodamine B wastewater, prepared with deionized water) or 20 mg / L of ciprofloxacin solution (simulated ciprofloxacin wastewater, prepared with deionized water), and take 20 ml of each in a beaker as the solution to be degraded. Weigh 20 mg of PVDF-GO / TiO2 composite films of different thicknesses prepared in Example 4, Example 6 and Example 7 (4 ml PVDF-GO / TiO2, 10 ml PVDF-GO / TiO2 and 18 ml PVDF-GO / TiO2) and place them in rhodamine B or ciprofloxacin (antibiotic) solution and place them under light (full spectrum, light intensity of 1000 W / cm 2 ) and stirring (1000rpm), the piezoelectric photocatalytic degradation experiment was carried out, the degradation time was 120min, 3ml of degradation solution was taken every 30min during the degradation process, and the absorbance of the degradation solution sample was tested on an ultraviolet visible spectrophotometer (UV-2600). After the test, the degradation solution sample was poured back into the beaker. The ratio of the absorbance at each time point in each group to the original absorbance (before degradation) was calculated, and the results are shown in Figure 6 , Figure 6 Figure A shows the effect of piezoelectric photocatalytic degradation of rhodamine B, and Figure B shows the effect of piezoelectric photocatalytic degradation of ciprofloxacin.

[0098] from Figure 6 It can be seen that 4ml PVDF-GO / TiO2 composite film has the best piezoelectric photocatalytic degradation ability. In the degradation experiment of rhodamine B, the degradation rate can reach 98.3% after 30 minutes of reaction, and in the degradation experiment of ciprofloxacin, the degradation rate can reach 95.2% after 120 minutes of reaction.

[0099] (2) The production of active oxygen and hydroxyl radicals of PVDF-GO / TiO2 composite films of different thicknesses (4 ml PVDF-GO / TiO2, 10 ml PVDF-GO / TiO2 and 18 ml PVDF-GO / TiO2) under the combined action of piezoelectricity and light was tested. The testing method was the same as that in Example 8.

[0100] The specific experimental steps are as follows: 20 mg of PVDF-GO / TiO2 composite films of different thicknesses were placed in 20 ml of TA solution or NBT solution, and then exposed to light (full spectrum, light intensity of 1000 W / cm 2 ) and stirring (1000rpm), the test was carried out. After 120min of piezoelectric photocatalytic degradation, 3ml of solution was taken and then tested on a fluorescence spectrophotometer (F97XP, China) or a UV-visible spectrophotometer (UV-2600). The test results are shown in Figure 7 .

[0101] from Figure 7It can be seen that the ·OH radicals and ·O2 - The production of free radicals is different, among which 4 ml PVDF-GO / TiO2 composite film produces ·OH radicals and ·O2 - The free radical content is relatively high, which is consistent with the degradation results. It can be seen that the thinner the film thickness, the greater the deformation can be formed under the same external force, thus forming a larger piezoelectric field to promote the transfer of electrons. In addition, the thinner the film, the more active sites of GO / TiO2 are exposed, which is conducive to the improvement of catalytic performance.

[0102] Example 10

[0103] A method for degrading organic pollutants in water by piezoelectric photocatalysis:

[0104] (1) Prepare 20 mg / L of rhodamine B solution (simulated rhodamine B wastewater, prepared with deionized water) or 20 mg / L of ciprofloxacin solution (simulated ciprofloxacin wastewater, prepared with deionized water), and take 20 ml of each in a beaker as the solution to be degraded. Weigh 20 mg of the PVDF-GO / TiO2 composite film prepared in Example 4 and place it in the rhodamine B or ciprofloxacin (antibiotic) solution, respectively, under light (full spectrum, light intensity of 1000 W / cm 2 ) and stirring (200, 600, 1000 or 1400rpm), the piezoelectric photocatalytic degradation experiment was carried out, the degradation time was 120min, 3ml of degradation solution was taken every 30min during the degradation process, and the absorbance of the degradation solution sample was tested on an ultraviolet visible spectrophotometer (UV-2600). After the test, the degradation solution sample was poured back into the beaker. The ratio of the absorbance at each time point in each group to the original absorbance (before degradation) was calculated, and the results are shown in Figure 8 , Figure 8 Figure A shows the effect of piezoelectric photocatalytic degradation of rhodamine B, and Figure B shows the effect of piezoelectric photocatalytic degradation of ciprofloxacin.

[0105] from Figure 8 It can be seen that when the stirring speed is greater than or equal to 1000rpm, the PVDF-GO / TiO2 composite film exhibits a high piezoelectric photocatalytic degradation ability. Under the conditions of illumination and stirring speed of 200, 600, 1000 and 1400rpm, the degradation rates of the PVDF-GO / TiO2 composite film in the degradation of Rhodamine B experiment were 80.9%, 93.2%, 99.3% and 99.1% after 60min of reaction; in the degradation of ciprofloxacin experiment, the degradation rates were 58.2%, 83.2%, 95.2% and 94.4% after 120min of reaction.

[0106] (2) The production of active oxygen and hydroxyl radicals of the PVDF-GO / TiO2 composite film prepared in Example 4 under the combined action of piezoelectricity and light was tested in the same manner as in Example 8.

[0107] The specific experimental steps are as follows: 20 mg of PVDF-GO / TiO2 composite film was placed in 20 mL of TA solution or NBT solution and illuminated (full spectrum, light intensity of 1000 W / cm 2 ) and stirring (200, 600, 1000 and 1400 rpm) conditions, the test was carried out. After 120 min of piezoelectric photocatalytic degradation, 3 ml of the solution was taken and then tested on a fluorescence spectrophotometer (F97XP, China) or a UV-visible spectrophotometer (UV-2600). The test results are shown in Fig. 9 .

[0108] from Fig. 9 It can be seen that the PVDF-GO / TiO2 composite film generates ·OH radicals and ·O2 at different rotation speeds. - The production of free radicals is different. When the stirring speed is greater than or equal to 1000 rpm, the ·OH free radicals and ·O2 produced by PVDF-GO / TiO2 - The free radical content is relatively high, which is basically consistent with the degradation results. This is because as the stirring speed increases, the external force on the film increases accordingly, thus forming an enhanced piezoelectric field and promoting the process of generating active oxygen.

[0109] Comparative Example 3

[0110] A method for degrading organic pollutants in water by piezoelectric photocatalysis:

[0111] Prepare 20 mg / L of Rhodamine B solution (simulated Rhodamine B wastewater, prepared with deionized water) or 20 mg / L of ciprofloxacin solution (simulated ciprofloxacin wastewater, prepared with deionized water), and take 20 ml of each in a beaker as the solution to be degraded. 20 mg of PVDF (i.e., PVDF-HFP), PVDF-GO (prepared in Comparative Example 1), PVDF-TiO2 (prepared in Comparative Example 2), and PVDF-GO / TiO2 composite film (prepared in Example 4) were placed in Rhodamine B or ciprofloxacin (antibiotic) solution and illuminated (full spectrum, light intensity of 1000 W / cm 2 ) and stirring (1000rpm), the piezoelectric photocatalytic degradation experiment was carried out, the degradation time was 120min, 3ml of degradation solution was taken every 30min during the degradation process, and the absorbance of the degradation solution sample was tested on an ultraviolet visible spectrophotometer (UV-2600). After the test, the degradation solution sample was poured back into the beaker. The ratio of the absorbance at each time point in each group to the original absorbance (before degradation) was calculated, and the results are shown in Fig.10 (Degradation effect of Rhodamine B) and Fig.11 (Degradation effect of ciprofloxacin).

[0112] from Fig.10 and Fig.11 It can be seen that the PVDF-GO / TiO2 composite film has the best piezoelectric photocatalytic degradation ability. In the degradation experiment of rhodamine B, the degradation rate can reach 99.3% after 60 minutes of reaction, while the degradation rates of PVDF, PVDF-GO and PVDF-TiO2 are 42.1%, 57.7% and 74.9%, respectively. In the degradation experiment of ciprofloxacin, the degradation rate of PVDF-GO / TiO2 composite film after 120 minutes of reaction is 95.2%, while the degradation rates of PVDF, PVDF-GO and PVDF-TiO2 are 30.5%, 46.8% and 79.9%, respectively. It can be seen that the addition of GO and TiO2 significantly improves the catalytic activity of PVDF. On the one hand, it is because the photocatalyst can excite more photogenerated electron-hole pairs under light to promote the generation of active oxygen. On the other hand, it is because GO and TiO2 can induce the formation of β phase of PVDF to improve the piezoelectric response ability of the catalyst.

[0113] Comparative Example 4

[0114] Preparation of non-porous PVDF-GO / TiO2 film:

[0115] (1) 0.477 g of PVDF-HFP particles were placed in 12 ml of DMAC (dimethylacetamide) solution and stirred until dissolved to obtain a precursor solution.

[0116] (2) Add TiO2 (the amount of TiO2 is 10% of the mass of PVDF-HFP) and 1 ml of GO dispersion (the mass ratio of GO to water in the GO dispersion is 5:95) to the precursor solution, stir until uniformly dispersed, and obtain a PVDF-GO / TiO2 mixed solution.

[0117] (3) 4 ml of the PVDF-GO / TiO2 mixed solution was poured into a 10 cm × 10 cm glass mold and dried at 80 °C for 6 h to obtain a PVDF-GO / TiO2 composite film, which was recorded as nonporous PVDF-GO / TiO2.

[0118] Comparative Example 5

[0119] Common phase separation method for preparing porous PVDF-GO / TiO2 film:

[0120] (1) 0.477 g of PVDF-HFP particles were placed in 12 ml of DMAC (dimethylacetamide) solution and stirred until dissolved to obtain a precursor solution.

[0121] (2) Add TiO2 (the amount of TiO2 is 10% of the mass of PVDF-HFP) and 1 ml of GO dispersion (the mass ratio of GO to water in the GO dispersion is 5:95) to the precursor solution, stir until uniformly dispersed, and obtain a PVDF-GO / TiO2 mixed solution.

[0122] (3) 4 ml of the PVDF-GO / TiO2 mixed solution was poured into a 10 cm × 10 cm glass mold, and water was sprayed on its surface until a film was formed to obtain a PVDF-GO / TiO2 composite film, which was recorded as porous PVDF-GO / TiO2.

[0123] Comparative Example 6

[0124] A method for degrading organic pollutants in water by piezoelectric photocatalysis:

[0125] Prepare 20 mg / L Rhodamine B solution (simulate Rhodamine B wastewater, use deionized water for preparation), take 20 ml in a beaker as the solution to be degraded. 20 mg of non-porous PVDF-GO / TiO2 (prepared in Comparative Example 4), porous PVDF-GO / TiO2 (prepared in Comparative Example 5) and PVDF-GO / TiO2 (prepared in Example 4) were placed in the Rhodamine B solution and illuminated (full spectrum, light intensity of 1000 W / cm 2 ) and stirring (1000rpm), the piezoelectric photocatalytic degradation experiment was carried out, the degradation time was 120min, 3ml of degradation solution was taken every 30min during the degradation process, and the absorbance of the degradation solution sample was tested on an ultraviolet visible spectrophotometer (UV-2600). After the test, the degradation solution sample was poured back into the beaker. The ratio of the absorbance at each time point in each group to the original absorbance (before degradation) was calculated, and the results are shown in Fig.12 (Degradation effect of Rhodamine B).

[0126] from Fig.12 It can be seen that the PVDF-GO / TiO2 composite film has the best piezoelectric photocatalytic degradation ability. In the degradation experiment of Rhodamine B, the degradation rate can reach 99.3% after 30 minutes of reaction, while the degradation rates of non-porous PVDF-GO / TiO2 and porous PVDF-GO / TiO2 are 6.9% and 82.3%, respectively. It further shows that the film obtained by the preparation method of the present invention can show higher catalytic activity than the film obtained by other methods.

[0127] Comparative Example 7

[0128] A method for preparing a PVDF-C / TiO2 composite film:

[0129] (1) 0.477 g of PVDF-HFP particles were placed in 12 ml of acetone, heated at 60° C. and stirred until dissolved, and then 0.477 g of deionized water (the mass ratio of PVDF-HFP, acetone and water was 1:20:1) was added and mixed evenly to obtain a precursor solution.

[0130] (2) Add TiO2 (the amount of TiO2 is 10% of the mass of PVDF-HFP) and 10 mg of carbon black to the precursor solution and stir until it is evenly dispersed to obtain a PVDF-C / TiO2 mixed solution.

[0131] (3) Pour 4 ml of the PVDF-C / TiO2 mixed solution into a glass bottle and spray it on the surface of a 10 cm × 10 cm aluminum foil to obtain a PVDF-C / TiO2 composite film, recorded as PVDF-C / TiO2.

[0132] Comparative Example 8

[0133] A method for preparing a PVDF-GO / BaTiO3 composite film:

[0134] (1) 0.477 g of PVDF-HFP particles were placed in 12 ml of acetone, heated at 60° C. and stirred until dissolved, and then 0.477 g of deionized water (the mass ratio of PVDF-HFP, acetone and water was 1:20:1) was added and mixed evenly to obtain a precursor solution.

[0135] (2) Add BaTiO3 (the amount of BaTiO3 is 10% of the mass of PVDF-HFP) and 0.1 ml of GO dispersion (the mass ratio of GO to water in the GO dispersion is 5:95) to the precursor solution, stir until uniformly dispersed, and obtain a PVDF-GO / BaTiO3 mixed solution.

[0136] (3) 4 ml of the PVDF-GO / BaTiO3 mixed solution was poured into a glass bottle and sprayed on the surface of a 10 cm × 10 cm aluminum foil to obtain a PVDF-GO / BaTiO3 composite film, recorded as PVDF-GO / BaTiO3.

[0137] Comparative Example 9

[0138] A method for degrading organic pollutants in water by piezoelectric photocatalysis:

[0139] Prepare 20 mg / L Rhodamine B solution (simulate Rhodamine B wastewater, use deionized water for preparation), take 20 ml in a beaker as the solution to be degraded. Place 20 mg of PVDF-C / TiO2 (prepared in Comparative Example 7), PVDF-GO / BaTiO3 (prepared in Comparative Example 8) and PVDF-GO / TiO2 (prepared in Example 4) in the Rhodamine B solution and irradiate with light (full spectrum, light intensity of 1000 W / cm 2 ) and stirring (1000rpm), the piezoelectric photocatalytic degradation experiment was carried out, the degradation time was 120min, 3ml of degradation solution was taken every 30min during the degradation process, and the absorbance of the degradation solution sample was tested on an ultraviolet visible spectrophotometer (UV-2600). After the test, the degradation solution sample was poured back into the beaker. The ratio of the absorbance at each time point in each group to the original absorbance (before degradation) was calculated, and the results are shown in Fig.13 (Degradation effect of Rhodamine B).

[0140] from Fig.13 It can be seen that the PVDF-GO / TiO2 composite film has the best piezoelectric photocatalytic degradation ability. In the degradation experiment of Rhodamine B, the degradation rate can reach 99.3% after 30 minutes of reaction, while the degradation rates of PVDF-C / TiO2 and PVDF-GO / BaTiO3 are 65.8% and 40.0%, respectively, indicating that GO and TiO2 can exert better catalytic performance as fillers.

[0141] The embodiments described above are only descriptions of the preferred modes of the present invention, and are not intended to limit the scope of the present invention. Without departing from the design spirit of the present invention, various modifications and improvements made to the technical solutions of the present invention by ordinary technicians in this field should all fall within the protection scope determined by the claims of the present invention.

Claims

1. A method for preparing a PVDF-GO / TiO2 composite film, characterized in that: The following steps are involved: PVDF is added to an organic solvent to dissolve, and then water is added and mixed to obtain a precursor solution; TiO2 and GO dispersions are added to the precursor solution and dispersed evenly to obtain a mixed solution, and the mixed solution is sprayed on the surface of the substrate to obtain the PVDF-GO / TiO2 composite film.

2. The preparation method according to claim 1, characterized in that: The PVDF includes PVDF-HFP; The usage ratio of the PVDF, organic solvent and water is 0.477 g:12 ml:0.477 ml; The amount of TiO2 is 5-15% of the mass of PVDF; The dosage ratio of the PVDF and GO dispersion is 0.477 g: 0.1-1 ml; The proportion of GO in the GO dispersion is 5 wt %.

3. The preparation method according to claim 1, characterized in that: The ratio of the spraying amount of the mixed solution to the area of ​​the substrate is 4-18 ml: 100 cm 2 .

4. A PVDF-GO / TiO2 composite film prepared by the preparation method according to any one of claims 1 to 3.

5. Use of the PVDF-GO / TiO2 composite film according to claim 4 in photocatalytic degradation of organic pollutants.

6. The use according to claim 5, characterized in that: The organic pollutants include dyes or antibiotics.

7. A method for degrading organic pollutants in water by piezoelectric photocatalysis, characterized in that: The following steps are involved: The PVDF-GO / TiO2 composite film according to claim 4 is placed in an aqueous solution containing organic pollutants, and piezoelectric photocatalytic degradation is performed under illumination and stirring.

8. The method according to claim 7, characterized in that The illumination is full spectrum illumination with a light intensity of 1000W / cm 2 ; The stirring speed is 1000-1400 rpm.

Citation Information

Patent Citations

  • Preparation method of nanometer photocatalyst film for degrading organic matter in waste water

    CN101648148A

  • Preparation method of power generating-energy storing porous film supported photocatalyst composite material

    CN108745416A

  • Preparation method, application and repair method of PVDF / TiO2 composite photocatalytic membrane

    CN111905811A

  • Preparation method and application of novel photocatalytic composite membrane

    CN112221359A

  • Photothermal-pyroelectric-photocatalytic composite film catalyst system as well as preparation method and application thereof

    CN118513086A